Anterior Tragal Crease Is Associated With Atherosclerosis: A Study Evaluating Carotid Artery Intima–Media Thickness. (September 2017) - Rerknimitr, Pawinee; Pongpairoj, Korbkarn; Kumtornrat, Chanat; Panchaprateep, Ratchathorn; Hurst, Cameron P.; Chutinet, Aurauma; Asawanonda, Pravit; Suwanwela, Nijasri C.
The utility of the ear crease sign, anterior tragal crease (ATC), as a marker of atherosclerosis is yet to be established. The intima–media thickness of the common carotid artery (IMT-CCA) has been used as a noninvasive surrogate marker for atherosclerosis. History of traditional risk factors for atherosclerosis was obtained from 147 volunteers; ear examination was also performed and venous blood was drawn for laboratory analysis. The volunteers then underwent an ultrasonography measurement of the IMT-CCA. In univariate analysis, presence of ATC, age, underlying hypertension, diabetes mellitus, ischemic heart disease, cerebrovascular disease, cigarette smoking, low-density lipoprotein, and high-sensitivity C-reactive protein were significantly associated with the IMT-CCA. Further multivariate analysis confirmed a significant association between the presence of ATC and IMT-CCA, when adjusted for other factors (adjusted βATC = .010, 95% confidence interval: 0.0021-0.019). Anterior tragal crease is a potential clinical sign that can predict atherosclerosis. The sign is easily recognizable and may help health-care professionals to identify those at risk of atherosclerosis, especially in people with no clinical signs of the disease.